Transcolonial Maghreb : imagining Palestine in the era of decolonization - Harrison, Olivia C., 1980- (Cultural memory in the present., 2016)
Transcolonial Maghreb offers the first thorough analysis of the ways in which Moroccan, Algerian, and Tunisian writers have engaged with the Palestinian question and the Palestinian-Israeli conflict for the past fifty years. Arguing that Palestine has become the figure par excellence of the colonial in the purportedly postcolonial present, the book reframes the field of Maghrebi studies to account for transversal political and aesthetic exchanges across North Africa and the Middle East.